2022
DOI: 10.1371/journal.pmed.1003965
|View full text |Cite
|
Sign up to set email alerts
|

Brain-based measures of nociception during general anesthesia with remifentanil: A randomized controlled trial

Abstract: Background Catheter radiofrequency (RF) ablation for cardiac arrhythmias is a painful procedure. Prior work using functional near-infrared spectroscopy (fNIRS) in patients under general anesthesia has indicated that ablation results in activity in pain-related cortical regions, presumably due to inadequate blockade of afferent nociceptors originating within the cardiac system. Having an objective brain-based measure for nociception and analgesia may in the future allow for enhanced analgesic control during sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Past studies from our group have shown a consistent functional dissociation—inverse correlation in fNIRS hemodynamic response—between S1 and mPFC/Brodmann area 10 during nociceptive stimuli, but not innocuous stimuli, in both conscious and unconscious patients 1 , 6 . This functional dissociation (negative relationship between the two regions) was found during pain but not auditory stimuli and diminished following morphine and remifentanil 4 , 12 . Therefore, evaluating the functional relationship between these two cortices during surgery using functional connectivity (FC) metric could identify nociceptive signaling to the brain.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Past studies from our group have shown a consistent functional dissociation—inverse correlation in fNIRS hemodynamic response—between S1 and mPFC/Brodmann area 10 during nociceptive stimuli, but not innocuous stimuli, in both conscious and unconscious patients 1 , 6 . This functional dissociation (negative relationship between the two regions) was found during pain but not auditory stimuli and diminished following morphine and remifentanil 4 , 12 . Therefore, evaluating the functional relationship between these two cortices during surgery using functional connectivity (FC) metric could identify nociceptive signaling to the brain.…”
Section: Introductionmentioning
confidence: 61%
“…1,6 This functional dissociation (negative relationship between the two regions) was found during pain but not auditory stimuli and diminished following morphine and remifentanil. 4,12 Therefore, evaluating the functional relationship between these two cortices during surgery using functional connectivity (FC) metric could identify nociceptive signaling to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…FNIRS is an innovative neuroimaging technique for measuring hemodynamic changes during brain activation [ 41 ]. fNIRS has the characteristics of portability, wireless nature and lightweight, which can be used as an objective index to evaluate changes in pain [ 42 ]. A recent study used fNIRS to evaluate the effect of exercise on the severity of pain, and the results showed that there was a significant difference in the activation of the prefrontal cortex before and after exercise [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…(b) Compared with placebo (blue curve). The administration of remifentanil (black curve) reduced the mPFC and S1 responses to invasive surgical procedures (cardiac ablation) in patients under general anesthesia 94 . fNIRS-derived cortical response is attenuated by opioids.…”
Section: Functional Near-infrared Spectroscopy (Fnirs) – a Potential ...mentioning
confidence: 99%
“…Findings from our prior fNIRS datasets are consistent with a nociceptive pain signature being measured. 81 84 , 94 96 Acute pain measures are important in the anesthesia setting as they relate to measures of specific nociceptive inducing procedures (e.g., cutting, cauterizing, scraping, stretching, etc.). In Fig.…”
Section: Functional Near-infrared Spectroscopy (Fnirs) – a Potential ...mentioning
confidence: 99%